Contributions of the medial prefrontal cortex to social influence in economic decision-making - Apps, M; Ramnani, N (Oxford University Press, 2017)
Economic decisions are guided by highly subjective reward valuations (SVs). Often these SVs are overridden when individuals conform to social norms. Yet, the neural mechanisms that underpin the distinct processing of such normative reward valuations (NV) are poorly understood. The dorsomedial and ventromedial portions of the prefrontal cortex (dmPFC/vmPFC) are putatively key regions for processing social and economic information respectively. However, the contribution of these regions to economic decisions guided by social norms is unclear. Using fMRI and computational modelling we examine the neural mechanisms underlying the processing of SVs and NVs. Subjects (n = 15) indicated either their own economic preferences or made similar choices based on a social norm - learnt during a training session. We found that that the vmPFC and dmPFC make dissociable contributions to the processing of SV and NV. Regions of the dmPFC processed only the value of rewards when making normative choices. In contrast, we identify a novel mechanism in the vmPFC for the coding of value. This region signalled both subjective and normative valuations, but activity was scaled positively for SV and negatively for NV. These results highlight some of the key mechanisms that underpin conformity and social influence in economic decision-making.